2017
DOI: 10.3892/ol.2017.5590
|View full text |Cite
|
Sign up to set email alerts
|

Expression of inositol-requiring enzyme 1β is downregulated in colorectal cancer

Abstract: The endoplasmic reticulum stress inositol-requiring enzyme (IRE) 1α/X-box binding protein (XBP) 1 signaling pathway is involved in the tumorigenesis of breast and prostate cancer. Mucin 2 (MUC2) protects colon tissues from the formation of tumors. In human colorectal cancer (CRC) the role of IRE1α, and its analogue, IRE1β, has yet to be elucidated. In the present study, the expression levels of IRE1α, IRE1β, un-spliced XBP1u, spliced XBP1s and MUC2 in surgically resected cancerous and adjacent non-cancerous ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Failing to move the C-terminal peptide of mucin-2 during posttranslation may interefere with the mobility of mucin-2, which could be the reason of the overaccumulation of aberrant mucin-2 in the ER lumen (Tsuru et al 2013). Consistently, it has been found that there was downregulated IRE1β expression in colorectal adenocarcinomas compared with normal colon (Jiang et al 2017). Clinical studies based on archived tumor tissues demonstrate that the levels of expression of specific ER stress markers can work as predictors of cancer (summarized in Table 1).…”
Section: Evidence Of Upr Involvement In Cancermentioning
confidence: 80%
“…Failing to move the C-terminal peptide of mucin-2 during posttranslation may interefere with the mobility of mucin-2, which could be the reason of the overaccumulation of aberrant mucin-2 in the ER lumen (Tsuru et al 2013). Consistently, it has been found that there was downregulated IRE1β expression in colorectal adenocarcinomas compared with normal colon (Jiang et al 2017). Clinical studies based on archived tumor tissues demonstrate that the levels of expression of specific ER stress markers can work as predictors of cancer (summarized in Table 1).…”
Section: Evidence Of Upr Involvement In Cancermentioning
confidence: 80%
“…IRE1β has been revealed to be involved in cell apoptosis (27). In a previous study, it was reported that IRE1β and MUC2 expression are downregulated in human colonic tissues (44). These results indicated that IRE1β serves an important role in the pathogenesis of colitis and tumors.…”
Section: Discussionmentioning
confidence: 94%
“…IRE1α serves a protective role against ER stress and colitis (24,40). The IRE1-XBP1 signaling pathway serves a pivotal role in cell survival under conditions of ER stress and is associated with tumorigenesis of various cancer types (41)(42)(43)(44). In the current study, mRNA expression of IRE1α, XBP1u and XBP1s and IRE1α protein expression were compared in tumor and normal tissues.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…31 A more recent study showed no significant differences in XBP1 (U) and XBP1(S) gene and protein expression between human colorectal cancerous tissues and the adjacent normal tissues. 32 Only one study has shown low expression of XBP1 in human prostate cancer. 33 However, the study did not differentiate between XBP1 (S) and XBP1 (U) mRNA expression levels.…”
Section: Discussionmentioning
confidence: 99%